Peningkatan Literasi Digital Guru PAUD melalui Pelatihan Video Edukatif Berbasis Digital Learning - Ratna Wahyu Pusari; Coryza Nursyahbani; M. Aniq Khairul Basyar; Arif Budiman (Abdimas Indonesian Journal, 2026)
The rapid development of digital technology requires early childhood education teachers to possess adequate digital literacy competencies to support innovative and meaningful learning. However, the needs assessment conducted in Kedungjati Village, Grobogan Regency, revealed that most preschool teachers had limited skills in utilizing digital technology and producing educational video media independently. This community service program aimed to improve teachers’ digital literacy through training and mentoring in developing educational videos based on digital learning principles. The program employed a participatory approach combined with a learning-by-doing method, including needs assessment, training, mentoring, classroom implementation, and evaluation stages. Participants consisted of 50 preschool teachers affiliated with IGTKI and Himpaudi organizations. Evaluation was conducted using pre-tests, post-tests, observations, questionnaires, and documentation. The results indicated a significant improvement in teachers’ digital literacy competencies, with average scores increasing from 58 to 86, representing a 48.27% improvement. Participants successfully produced four locally contextualized educational videos that were ready for classroom use. The implementation of these videos in learning activities increased children's learning engagement by 21%. Furthermore, questionnaire results showed that 90% of participants perceived the training as highly beneficial, 88% reported increased confidence in using digital technology, and 85% expressed willingness to independently develop educational videos in the future. These findings demonstrate that the program effectively enhanced teachers’ digital competencies and contributed to improving the quality of technology-based early childhood education..